Are recent attempts to quit smoking associated with reduced drinking in England? A cross-sectional population survey. (December 2016) - Brown, Jamie; West, Robert; Beard, Emma; Brennan, Alan; Drummond, Colin; Gillespie, Duncan; Hickman, Matthew; Holmes, John; Kaner, Eileen; Michie, Susan
Abstract Background Alcohol consumption during attempts at smoking cessation can provoke relapse and so smokers are often advised to restrict their alcohol consumption during this time. This study assessed at a population-level whether smokers having recently initiated an attempt to stop smoking are more likely than other smokers to report i) lower alcohol consumption and ii) trying to reduce their alcohol consumption. Method Cross-sectional household surveys of 6287 last-year smokers who also completed the Alcohol Use Disorders Identification Test consumption questionnaire (AUDIT-C). Respondents who reported attempting to quit smoking in the last week were compared with those who did not. Those with AUDIT-C≥5 were also asked if they were currently trying to reduce the amount of alcohol they consume. Results After adjustment for socio-demographic characteristics and current smoking status, smokers who reported a quit attempt within the last week had lower AUDIT-C scores compared with those who did not report an attempt in the last week (βadj = −0.56, 95 % CI = −1.08 to −0.04) and were less likely to be classified as higher risk (AUDIT-C≥5: ORadj = 0.57, 95 % CI = 0.38 to 0.85). The lower AUDIT-C scores appeared to be a result of lower scores on the frequency of 'binge' drinking item (βadj = −0.25, 95 % CI = −0.43 to −0.07), with those who reported a quit attempt within the last week compared with those who did not being less likely to binge drink at least weekly (ORadj = 0.54, 95 % CI = 0.29 to 0.999) and more likely to not binge drink at all (ORadj = 1.70, 95 % CI = 1.16 to 2.49). Among smokers with higher risk consumption (AUDIT-C≥5), those who reported an attempt to stop smoking within the last week compared with those who did not were more likely to report trying to reduce their alcohol consumption (ORadj = 2.98, 95 % CI = 1.48 to 6.01). Conclusion Smokers who report starting a quit attempt in the last week also report lower alcohol consumption, including less frequent binge drinking, and appear more likely to report currently attempting to reduce their alcohol consumption compared with smokers who do not report a quit attempt in the last week.